The imagined underworld: sex, crime, and vice in porfirian Mexico City - Garza, James Alex (University of Nebraska Press, 2007)
Introduction -- Charting the imagined city -- The terror of Peralvillo, "El Chalequero" -- Love, betrayal, and death in the underworld -- Organized crime and the porfirian state -- Disease, decay, and the strange case of Federico Abrego and María Barrera -- Politics, corruption, and the Arnulfo Arroyo affair -- Conclusion -- Notes -- Bibliography -- Index